2019
DOI: 10.1177/1559325818807781
|View full text |Cite
|
Sign up to set email alerts
|

National Trends of Bladder Cancer and Trihalomethanes in Drinking Water: A Review and Multicountry Ecological Study

Abstract: We examined trends in incidence of bladder cancer in 8 countries in the 45+ years since trihalomethanes (THMs) were detected in chlorinated drinking water. Total trihalomethanes (TTHMs) are the principal regulated disinfection by-products (DBPs) along with halogenated acetic acids (HAAs). Numerous epidemiological studies have examined exposure to TTHMs and associations with bladder cancer. Concentrations of TTHM have declined in most of the 8 countries that were studied as has smoking prevalence. Incidences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
0
16
0
6
Order By: Relevance
“…But, as the liver and kidney are the most common target organs for toxicity, they are most likely to develop tumors in humans (5). In a recently published systematic review with the aim of detecting the populations and regions vulnerable to bladder and colorectal cancer due to exposure of DBPs, the incidence of the mentioned cancers among different groups of people have been discussed; furthermore, it has been determined that socio-demographic characteristics may play an important role as risk factors (40)(41)(42)(43)(44)(45).…”
Section: Resultsmentioning
confidence: 99%
“…But, as the liver and kidney are the most common target organs for toxicity, they are most likely to develop tumors in humans (5). In a recently published systematic review with the aim of detecting the populations and regions vulnerable to bladder and colorectal cancer due to exposure of DBPs, the incidence of the mentioned cancers among different groups of people have been discussed; furthermore, it has been determined that socio-demographic characteristics may play an important role as risk factors (40)(41)(42)(43)(44)(45).…”
Section: Resultsmentioning
confidence: 99%
“…Guidelines and standards exist for the major halogenated DBPs on the basis of conservative assumptions with large margins of safety and on the basis of lifetime exposures. THMs are not carcinogenic in bioassay animal tests conducted in water rather than in corn oil (Cotruvo & Amato 2019).…”
Section: Balancing Risksmentioning
confidence: 95%
“…Although several of these organic halogenated byproducts have been shown to cause cancer in laboratory animals given high doses, evidence for effects in humans remains inconclusive even after significant research (Cotruvo & Amato 2019, Goslan & Hassard 2019, Hrudey & Fawell 2015, Hrudey et al 2015). A few epidemiological studies have suggested a small association between THMs and bladder cancer in men, but the evidence is insufficient to demonstrate that the association is causal (Cotruvo & Amato 2019). So, while it is reasonable to take steps to minimize DBP formation from supplemental disinfection, control of Legionella should never be compromised, especially in high‐risk facilities.…”
Section: Balancing Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…THMs are a cause of great concern in drinking WTPs due to their probable cancer and non-cancer risk on human health 16,17 . Number of studies all across the world has reported cancer and non-cancer risk of THMs for individual age groups, and for male and female as well 2,18–21 .…”
Section: Introductionmentioning
confidence: 99%